2021
DOI: 10.1093/jamiaopen/ooab023
|View full text |Cite
|
Sign up to set email alerts
|

Designing and evaluating contextualized drug–drug interaction algorithms

Abstract: Objective Alert fatigue is a common issue with off-the-shelf clinical decision support. Most warnings for drug–drug interactions (DDIs) are overridden or ignored, likely because they lack relevance to the patient’s clinical situation. Existing alerting systems for DDIs are often simplistic in nature or do not take the specific patient context into consideration, leading to overly sensitive alerts. The objective of this study is to develop, validate, and test DDI alert algorithms that take adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…This study confirms the importance of context in limiting a large proportion of false positives in DDI detection (5). This gives useful guidance to conduct studies that attempt to determine the frequency of DDI on real-world data or for critical appraisal of such studies.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This study confirms the importance of context in limiting a large proportion of false positives in DDI detection (5). This gives useful guidance to conduct studies that attempt to determine the frequency of DDI on real-world data or for critical appraisal of such studies.…”
Section: Discussionsupporting
confidence: 73%
“…For a good detection of potential DDIs, a more contextualized definition of DDIs is also important and limits false positives (5). The context can be divided into drugrelated factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the results of Mille et al [ 30 ], the lack of DDI-specific screening intervals and lack of incorporation of context factors were identified, in both our quantitative evaluation and end-user survey, as the main barriers of our current DDI CDSS system. Recent studies already showed the potential of including patient-specific and context-specific characteristics into DDI CDSS algorithms on reducing the DDI alert burden [ 17 , 18 ]. Chou et al showed a reduction in DDI alerts by more than 50% [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies already showed the potential of including patient-specific and context-specific characteristics into DDI CDSS algorithms on reducing the DDI alert burden [ 17 , 18 ]. Chou et al showed a reduction in DDI alerts by more than 50% [ 17 ]. Alerts were reduced by up to 93.5% in the study of Horn and Ueng [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…DDIAs increase the workload of healthcare staff. Nevertheless, previous studies showed several strategies to reduce irrelevant DDIAs, including applying the pharmacist recommendations to review DDIs, considering context factors of diagnosis, patient age and laboratory value (19,20). DDIA systems reached high priority for implementation in ICU settings in Iran based on a previous Karajizadeh and et al's study (21).…”
Section: -Introductionmentioning
confidence: 99%